KIAT MEMBUAT PEMBELAJARAN IPS TERPADU MODEL CONNECTED BAGI GURU DI SEKOLAH DASAR - Sri Rahayu; Wibi Wijaya; Trina Febriani; Yanti Sri Wahyuni (Turast: Jurnal Penelitian dan Pengabdian, 2022)
Mastery of a teacher in conducting integrated learning is important in every lesson, especially in elementary schools. The achievement of learning carried out by a teacher cannot be separated from the learning models used. This community service activity is based on the fact that not all teachers in elementary schools master the learning material, this is because these teachers are graduates from multidisciplinary sciences. So that the learning carried out by the teacher experiences problems in the process of delivering material to students. The purpose of this activity is to provide training to teachers to master integrated social studies learning models that are in accordance with learning in the 21st century and especially learning during this pandemic. This training activity uses observation, interview and participant-centered methods through direct simulation techniques, and is followed by evaluation at the final stage of the activity. The output target generated in this activity is the development of an innovative integrated social studies learning model in the new normal era.